HAK MEMPEROLEH PENDIDIKAN SEBAGAI SALAH SATU UPAYA DALAM MENCERDASKAN KEHIDUPAN BANGSA - Hamzah, Muhammad; Mahelatu, Anggi Rizkina; Rajaa, Zulfaa Giusti (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
Education is a right that can be obtained by every citizen, both because he is a human being who has a mind and then develops himself and also because it is the need of every individual in following the times. The purpose of this research is to examine the rights of every person, especially citizens, in obtaining education amidst the rapid development of the times and will continue to grow and as a fulfilment of efforts in realising the noble goal of educating the nation's life. This research uses a normative juridical method, namely by using a examining literature & books along with laws and regulations related to the problem under study. Based on the review of the literature, it is found that education is an inherent right as an element that everyone must get in the process of one's development which will later give birth to quality generations that can maintain the values that exist in a society, many laws and regulations have been passed in order to fulfil the rights of everyone in obtaining education as a form of responsibility that the state provides. However, there are still difficulties for citizens to get their full rights. This is due to inadequate family economic factors, social conditions and the mindset of people who are less concerned about education, as well as unequal access to education to remote areas. Thus there are still many rights of citizens that need to be fought for as their right to education.